Analysis of Children's Emotional Development in Edutainment-Based Learning in Group B of Mbelin Gunana Early Childhood Education, Sei Bingai District, Langkat Regency - Sembiring, Vioren Timanta Br; Anggraini, Elya Siska (Jurnal Riset Ilmu Pendidikan, 2025)
Children’s emotional development must be appropriately stimulated, particularly through school environments. Edutainment-based learning offers an enjoyable and interactive approach to support this development. This study aims to explore emotional development in children through edutainment-based learning at Group B PAUD Mbelin Gunana, Sei Bingai District, Langkat Regency. A qualitative approach was employed using observation, interviews, and documentation as data collection techniques. The findings indicate that edutainment methods enhance children's self-confidence, social interaction skills, and emotional regulation. Activities such as singing, playing, and storytelling positively influence children's moods and learning motivation. Teachers play a key role in fostering a supportive atmosphere that enables children to express their emotions more openly. Thus, edutainment-based learning is proven effective in supporting children's emotional development and is recommended for broader implementation in early childhood education institutions.